2020
DOI: 10.1017/s1047951120001948
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between non-cardiac chest pain and internalizing problems in pre-school aged children

Abstract: Objective: Non-cardiac chest pain is a common and persistent problem for children; yet, typically, there is no clear medical cause. To date, no behavioural and/or psychological factors have been studied to explain chest pain in a pre-school paediatric sample. We hypothesized that pre-school children with medically unexplained chest pain would have higher rates of behavioural problems compared to healthy controls. Methods: We assessed 41 pre-school children with non-cardiac chest pain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In our study, in the preschool group and the school-age group, the incidence of non-cardiac chest pain was significantly higher than it in the adolescent group, respectively. This might be related to increasing levels of some behavioral comorbidities as described above ( 21 ). For clarifying the effects of demographic characteristics on the distribution of chest pain etiology, we will conduct prospective, multi-center and social psychology comprehensive research on children with chest pain in the future.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, in the preschool group and the school-age group, the incidence of non-cardiac chest pain was significantly higher than it in the adolescent group, respectively. This might be related to increasing levels of some behavioral comorbidities as described above ( 21 ). For clarifying the effects of demographic characteristics on the distribution of chest pain etiology, we will conduct prospective, multi-center and social psychology comprehensive research on children with chest pain in the future.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies showed that children with age over 12 years and in puberty are prone to chest pain ( 5 , 6 , 16 ). In 2020, Yoldaş T. et al ( 21 ) studied the relationship between non-cardiac chest pain and internalizing problems in pre-school aged children, they found that these children might be related to increasing levels of some behavioral comorbidities. In 2020, Aygun E et al ( 22 ) analyzed the etiology of 782 patients aged between 3 and 18 years with chest pain, they found that male patients were more prone to musculoskeletal and gastrointestinal systems diseases, while female patients were more prone to psychogenic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Overall internalizing behavior problems. Of six studies comparing children of employed and unemployed mothers [ 60 , 62 , 63 , 66 , 67 , 81 ], only Im and Vanderweele [ 67 ] found results linking employment to more IBP (especially in cases of absent or low paternal involvement). In contrast, when paternal involvement was high, employment was associated with less IBP.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, when paternal involvement was high, employment was associated with less IBP. In analyses of Yoldaş and colleagues [ 81 ] children of working mothers exhibited less IBP. Our corresponding meta-analysis including three studies [ 62 , 63 , 81 ] yielded a summary effect under the fixed-effects model ( OR = 0.868, P < 0.001), indicating that children of employed mothers exhibited less IBP (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation